Antibacterial Activity of Ethanol Extract Ointment of Tithonia diversifolia Against Staphylococcus aureus - Triana, Linda; Supardi, Rizal; Sutriswanto, Sutriswanto; Ratnawati, Gervacia Jenny; Sari, Emilda; Nurhayati, Etiek (Jurnal Laboratorium Khatulistiwa, 2025)
Skin infections caused by pathogenic bacteria such as Staphylococcus aureus remain a common health problem, and the need for safer alternative topical antibacterial agents continues to increase. This study aimed to evaluate the antibacterial activity of ethanol extract ointment of Tithonia diversifolia leaves with various concentrations formulated as a semi-solid topical preparation. A quasi-experimental design was used, and ointments were prepared at concentrations of 5%, 7%, 9%, 11%, 13%, 15%, 17%, 19%, and 21%. Antibacterial activity was tested using the well-diffusion method against Staphylococcus aureus. A total of 27 samples were tested with three replications. The results showed that the ointment produced inhibition zones ranging from 13.83 mm to 22.00 mm, with higher concentrations yielding greater inhibition. Repeated Measures ANOVA showed a significant difference among concentrations (p = 0.003), indicating that the increase in extract concentration significantly affected the antibacterial effectiveness. This study concludes that ethanol extract ointment of Tithonia diversifolia leaves demonstrates strong antibacterial activity against Staphylococcus aureus*, with effectiveness increasing proportionally with concentration.